Penerapan Metode K-Means Clustering Untuk Daging Ayam Buras - Miralda, Viya; Zarlis, Muhammad; Irawan, Eka (Building of Informatics, Technology and Science (BITS), 2020)
Free-range chicken is a local Indonesian poultry whose population is widely found in every region of Indonesia. However, the level of consumption of free-range chicken meat in North Sumatra Province is still relatively low. This research data contains data on the production of free-range chicken in North Sumatra Province. One data mining technique is clustering. Grouping itself is a method by grouping data. The data of this study contains data on the production of free-range chicken in North Sumatra Province which began in 2010, 2011, 2012, 2013, 2014, 2017. (7 years), and data obtained from the Directorate General of Animal Husbandry and Animal Health as well as on animal access to BPS Sumatra site North (Central Statistics Agency). The purpose of this study is to group Regencies / Cities in North Sumatra Province into 2 parts. These are the Regency / City group with high free-range chicken meat and Regency / City with low-free chicken meat. This can be a contribution of the provincial government of North Sumatra, Regency / City which is of more concern than free-range chicken based on the cluster that has been done. The results of this research are taken from 33 data of free-range chicken meat in regencies / cities in North Sumatra province, 3 high-level districts, namely: Mandailing Natal, Langkat, Serdang Bedagai and 30 other regencies / cities including